SECURITY ISSUES REGARDING ONLINE BANKING: WITH SPECIAL REFERENCE TO FEDERAL BANK - Irshad.M.K, Dr. R.Sathya Devi (International Journal of Research Science and Management, 2015)
The emergence of internet has opened a wide variety of avenues and information to the common man, which he can access from the comfortable home settings. Along with the facilities like shopping, booking tickets etc...Internet has also become a model for banking. Online banking was introduced in the early 80’s and from the time it has been introduced, many people have started availing its facilities. Now one does not have to wait in a long line at the bank or at some shopping centre or boutique. Online banking gives person facilities to view account statement, make money transfers from one account to other, and also to pay bills like electricity, phone etc…the best thing about online banking is that it is fast and available to a person in any part of the world, at any time he or she needs it. Security of a customer’s financial information is very important without which online banking could not operate. Financial institutions have setup various security processes to reduce the risk of unauthorized online access to a customer’s records. Federal bank is a major Indian commercial bank in the private sector, head quarters at aluva, Kochi, Kerala.